The Development of Soga Tingi (Ceriops tagal) Natural Dye Paste Material for Block Printing on Textiles - Hanifa Aisha Yasmin; Mochammad Sigit Ramadhan; Gina Shobiro Takao (PANGGUNG, 2025)
Block printing is a technique of carving motifs on a printing plate coated with dye and pressed repeatedly along the fabric to create patterns. One potential natural dye that can be applied is the Soga tingi (Ceriops tagal). In today’s textiles and fashion industries, the use of natural materials is increasing in line with the growing awareness of a sustainability lifestyle. This study aims to develop Soga tingi dye into the optimal paste formula for block printing techniques with fixation, plate material, and suitable fabrics. This research employs a mixed-methods approach, combining qualitative and quantitative data from literature reviews, field observations, interviews, and laboratory experiments. The results reveal the successful formulation of a Soga tingi natural dye paste with an optimal composition. The most effective thickening agent was found to be sodium alginate, a food-grade thickener used in a ratio of 10 g to 100 ml of liquid natural dye, resulting in a viscosity of 21,135 mPas. Thus, the block-printed cotton fabric made with the Soga tingi natural dye paste can be used for fashion products.